Higher Level Zinc Serum in Multibacillary Leprosy With Erythema Nodosum Leprosum compared to Patients Without Reaction - Kinanti Prabawaningrum; Linda Astari; Indropo Agusni (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Leprosy is an infectious disease that causes a redistribution of nutrients in the body, including zinc, and low food intake of zinc causes decreased serum zinc levels. The number of bacteria M. leprae in multibacillary (MB) type leprosy and acute inflammatory process in Erythema Nodosum Leprosum (ENL) reaction affect the levels of zinc. Purpose: To analyze differences in the results of serum zinc levels in MB patients without reactions and ENL. Methods: Cross sectional study was conducted on forty-eight patients with a diagnosis of MB leprosy in Dermato and venereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya. Patient's blood had been taken to examine serum zinc levels. Result: The mean serum zinc levels of MB patients without reaction 78.49 g/dL, while ENL 175.83 g/dL. Conclusion: The mean serum zinc levels of MB patients with ENL is higher than without reaction.Key words: MB leprosy, ENL, cross sectional, serum zinc.